Performance Finance from the Perspective of Standard Financial Ratio Limits and Good Corporate Governance in Banking Sector Shares - Amirudin, A.; Muchran, Muchriana; Rustan, R. (Manunggal Halim Jaya, 2024)
This research is expected to provide practical and theoretical benefits. And as a source of information about the influence of financial risk on financial performance. This research can be helpful for other researchers as material for further studies regarding issues related to the impact of financial risk on financial performance in banking companies listed on the Indonesian Stock Exchange (BEI). This research can be used as material for banking evaluations so that they can implement appropriate risk management strategies to improve banking performance. Studies referred to Laeli and Yulianto (2016) and Izdihar, Hassan, And Azlina (2017) show that good corporate governance can moderate the relationship between Non-Performing Loans and bank financial performance. Results contradict the study by Akbar and Lanjarsih (2019), which shows that good corporate governance can moderate the connection between non-non-performing loans and financial performance. This research aims to find out whether management projected risk NPL (Net et al. (Loan et al.), BOPO (Operating Costs) Against Operating Income) can affect the financial performance projected by Return on Assets (ROA). This research also aims to determine whether assessing Good Corporate Governance (GCG) can moderate management relationships risk and ROA. The data used in this research is quantitative; the data used is secondary data. The data analysis techniques used in this research are the classic assumption test, moderated regression analysis, t-test, and F test using SPSS Moderated Regression Analysis (MRA) software. The results of this study show that LDR has no effect and is negatively related to ROA. BOPO has no effect and is negatively related to ROA. NPL has no effect and is positively related to ROA. GCG Self-Assessment does not moderate NPL on ROA, with a negative relationship. GCG Self-Assessment does not moderate LDR on ROA and is positively related. GCG Self-Assessment does not moderate BOPO on ROA, with an antagonistic relationship.